Dense GNSS Profiles Across the Northwestern Tip of the India‐Asia Collision Zone: Triggered Slip and Westward Flow of the Peter the First Range, Pamir, Into the Tajik Depression. Issue 2 (20th February 2020) - Metzger, Sabrina; Ischuk, Anatoly; Deng, Zhiguo; Ratschbacher, Lothar; Perry, Mason; Kufner, Sofia‐Katerina; Bendick, Rebecca; Moreno, Marcos
Abstract: At the northwestern tip of the India‐Asia collision zone, the Pamir orocline overrides the Tajik Depression and the Tarim Basin and collides with the Tian Shan. Currently, the Pamir's northern edge exhibits localized shortening rates of 13–19 mm/yr. While the eastern Pamir and the Tarim Basin move northward nearly en block, north‐south shortening decreases westward along the Pamir front into the Tajik Depression. In the northeastern Tajik Depression, the wedge‐shaped crustal sliver of the Peter the First Range is squeezed between the dextral‐transpressive Vakhsh and the sinistral‐transpressive Darvaz faults. Global Navigation Satellite System (GNSS) data collected along two densely surveyed profiles detail the kinematics of north‐south shortening and westward lateral extrusion in the northwestern Pamir. The 2016 campaign data suggest a short‐duration dextral‐slip activation of the Darvaz fault, which we interpret as a far‐field effect triggered by the 2015, Mw 7.2 Sarez, Central Pamir earthquake. 2013–2015 interseismic GNSS velocities and kinematic modeling show that the Darvaz fault zone accommodates ~15 mm/yr sinistral shear and ~10 mm/yr fault‐normal extension below a locking depth of 9.0 + 0.4/−1.1 km. The Vakhsh fault shows shortening rates of 15 + 4/−2 mm/yr and dextral shear rates of 16 ±3 mm/yr. Jointly, these faults accommodate NW‐SE shortening and southwestward material flow out of the Peter the First Range into the Tajik Depression. Together with seismic and geologic data, our and published geodetic surveys showcase the prolonged interaction of shortening and lateral material flow out of a plateau margin. Plain Language Summary: The Pamir Mountains, Central Asia, are the result of the northward indentation of the Indian continent into Eurasia. In average, the Pamir Plateau is ~3, 000 m higher than the adjacent Tajik Depression to the west. We present time‐series of high‐precision point positioning data that show in great detail how the upper crust of the Pamir is flowing out into the lower lying Tajik Depression. This westward transport occurs on shallow‐dipping, low‐friction sedimentary layers that reach surface at the beginning of the Tian Shan Mountains further north. These sediments accommodate a total slip of around 2 cm, which is extremely high for continent‐continent plate boundaries. In addition, our data observed a few centimeters of slip on the Darvaz fault that most probably was triggered by a large earthquake occurring in some 200 km distance. Such phenomena have so far rarely been observed. Key Points: New survey‐GNSS data record gravity‐driven, lateral material flow out of the Pamir Plateau and shortening of the Tajik Basin deposits The Vakhsh fault accommodates 15 + 4/−2 mm/yr shortening and 16 ±3 mm/yr dextral shear, the Darvaz fault ~15 mm/yr sinistral shear The 2015 Mw 7.2 Sarez earthquake may have triggered ~2 cm of slip on the Darvaz fault reverse to its interseismic loading sense